2007
DOI: 10.1007/s11104-007-9239-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizas in agroforestry: spread and sharing of arbuscular mycorrhizal fungi between trees and crops: complementary use of molecular and microscopic approaches

Abstract: 17Both inoculants greatly improved the growth of the trees and colonization spread to the crops once 18 the trees were 6 months old. However, benefits of inoculation to crop growth were not observed due 19 to increased competition from the larger inoculated trees growing in a restricted soil volume. Of the 20 two inoculant fungi, Glomus etunicatum appeared to be more mobile as it spread more rapidly, 21 formed higher levels of colonization at increasing distances from the tree and was responsible for 22 most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
(21 reference statements)
2
42
0
2
Order By: Relevance
“…Root mycorrhizal infection had no effect on either P or K foliar contents under greenhouse conditions. As was observed for Rhizobium strain KWN35, it seems that the effectiveness of arbuscular mycorrhizal fungi isolate BEG 176 was also limited in the Bel Air soil whereas the same arbuscular mycorrhizal fungi has been demonstrated by Ingleby et al (2007) as being very efficient for improving the growth of C. calothyrsus cultivated in a sterilized loam/grit-sand mixture under greenhouse conditions. showed under controlled conditions that C. calothyrsus is dependent on mycorrhizal associations in P-deficient soil, and that mycorrhizal inoculation has the potential to enhance its growth and nodulation under these conditions.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Root mycorrhizal infection had no effect on either P or K foliar contents under greenhouse conditions. As was observed for Rhizobium strain KWN35, it seems that the effectiveness of arbuscular mycorrhizal fungi isolate BEG 176 was also limited in the Bel Air soil whereas the same arbuscular mycorrhizal fungi has been demonstrated by Ingleby et al (2007) as being very efficient for improving the growth of C. calothyrsus cultivated in a sterilized loam/grit-sand mixture under greenhouse conditions. showed under controlled conditions that C. calothyrsus is dependent on mycorrhizal associations in P-deficient soil, and that mycorrhizal inoculation has the potential to enhance its growth and nodulation under these conditions.…”
Section: Discussionmentioning
confidence: 57%
“…Prior to registration with The International Bank for the Glomeromycota (BEG), it was known by its isolate number 'Glomus etunicatum 1' and had been shown to form mycorrhizas abundantly under greenhouse conditions and promote the growth, shoot phosphorus and nodule dry mass of C. calothyrsus (Lesueur et al 2001;Ingleby et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…The fact that big T. cacao saplings benefited most of the association with G. sepium supports this hypothesis. Ingleby et al (2007) observed in a study, which we found after completing field work, that competition between Calliandra calothyrsus Meissner and annual crops in a limited growth space reduced the benefit of N 2 fixation by the legume tree to the crops. They also noted that mycelial growth rate of tropical AMF was relatively slow but even if the growth rate was the same in our barrels, it would have been fast enough to connect T. cacao and the legume tree saplings as their roots were intimately mixed.…”
Section: Dinitrogen Fixationmentioning
confidence: 73%
“…Thus, the uptake possibilities of mycorrhizal systems are currently more difficult to quantify than systems consisting of roots only. Where trees and their intercrops share mycorrhizal fungi (Ingleby et al, 2007;Shukla et al, 2012), there are also possibilities for transfer of nutrients between plants of the same and different species, and trees may act as reservoirs of inoculum for annual crops. The ability of mycorrhiza to increase nutrient uptake either due to their extensive foraging mycelium, or to their ability to access otherwise unavailable nutrients further extends the complexity of tree-crop interactions, especially as particular mycorrhizal associations can change the balance of plant species within mixed communities (van der Heijden and Wagg, 2013) and mycorrhiza are also implicated in water uptake (e.g.…”
Section: Roots and Their Symbiontsmentioning
confidence: 99%